Strategi Social Media Marketing Instagram Non Governmental Organization Untuk Meningkatkan Engagement - Adinda Putri Agilia; Dede Lilis Chaerowati (UNISBA Press, 2022)
Abstract . Indonesia is experiencing a lot of social problems that harm many people. Social problems that occur include social inequality, poverty, and ignorance. It is imperative to find a solution so that social life can return to balance. Berikan Protein Initiative is an NGO that has concerns in the field of health and alleviation of ignorance ready to help be at the forefront. Technological developments that present new media, one of which is Instagram, makes communication activities easier but requires a strategy to increase engagement. This study aims to analyze the management of Instagram @berikanprotein based on 4 (four) elements of social media marketing, discuss the engagement that Instagram @berikanprotein gets after carrying out a social media marketing strategy, examine the need for the development of Instagram @berikanprotein. The theory used is the theory of social media marketing, this research method uses qualitative research methods with a case study approach. The informants were determined by purposive sampling technique. The results of the research show (1) The management of the account Instagram @berikanprotein utilizes social media marketing strategies, in the content creation element it has not been able to invite the audience to fill out the protein meter and in the community building web element there is no large online community formed, (2) Engagement obtained by the account Instagram @berikanprotein is large, it can be seen from the number of interactions and visits on insights, (3) the development of the Instagram account @berikanprotein still needs to pay attention to being consistent in uploading content, evaluating and improving, as well as solicitations in hardselling protein meter content. Abstrak. Indonesia mengalami banyak sekali permasalahan-permasalahan sosial yang merugikan banyak orang. Masalah sosial yang terjadi, antara lain kesenjangan sosial, kemiskinan, serta kebodohan. Hal tersebut harus segera dicarikan solusinya agar kehidupan bermasyarakat dapat kembali seimbang. Berikan Protein Initiative merupakan sebuah NGO yang memiliki concern di bidang kesehatan dan pengentasan kebodohan siap membantu menjadi garda terdepan. Perkembangan teknologi yang menghadirkan media baru salah satunya adalah Instagram membuat kegiatan komunikasi semakin mudah namun memerlukan strategi untuk dapat meningkatkan engagement. Penelitian ini bertujuan menganalisis pengelolaan Instagram @berikanprotein berdasarkan 4 (empat) elemen social media marketing, membahas engagement yang didapatkan Instagram @berikanprotein setelah menjalankan strategi social media marketing, mengkaji perlunya pengembangan Instagram @berikanprotein. Teori yang digunakan adalah teori social media marketing, metode penelitian ini menggunakan metode penelitian kualitatif dengan dengan pendekatan studi kasus dan informan ditentukan dengan teknik purposive sampling. Hasil penelitian menunjukkan (1) Pengelolaan akun Instagram @berikan memanfaatkan strategi social media marketing, pada elemen content creation belum bisa mengajak audiens untuk mengisi protein meter dan pada elemen community building web belum adanya komunitas online besar yang terbentuk, (2) Engagement yang didapatkan akun Instagram @berikanprotein besar terlihat dari jumlah interaksi dan kunjungan pada insight, (3) Pengembangan akun Instagram @berikanprotein masih perlu memperhatikan konsisten dalam mengunggah konten, evaluasi dan perbaikan, serta ajakan dalam konten hardselling protein meter.